Teologi Perjanjian Dalam Perjanjian Lama: Fondasi Hubungan Allah Dan Rencana Keselamatan - Pelealu, Nadia; Selan, Yunus; Harti, Sri Dwi (Views : Jurnal Teologi dan Biblika, 2025)
This article discusses the concept of “convenant” in the Old Testament as the main framework for the relationship between God and His people. In Hebrew, convenant is called berith, and in Greek, diatheke, which indicates that a convenant is not only a legal bond, but also a reflection of God’s love and faithfulness to mankind. These convenants incolve several figures, including Adam, Noah, Abraham, Moses, and David, who share a common thread og God’s faithfulness in carrying out His plan of salvation for His people. Each convenant highlights various theological aspects, namely creation, salvation, elction, law, and kingdom. Thus, this article helps readers see that all these conevnants are fulfilles in Jesus Christ through the new convenant, where God’s law is no longer written on stone, but in the hearts of men. This study affirms that the convenant is the main foundation of biblical theology, which shows the relationship between God’s grace and man’s responsibility to live in obedience.